Psychological Evaluation of Non-Verbal Relational Communication - Sánchez Aragón, Rozzana (Pensando Psicología, 2014)
Relational communication represents the primary interaction mechanism between members of a close relationship, as it plays a role in developing bonds—either of intimacy or hostility—between the people in the relationship across both communication channels (verbal and non-verbal). Due to its complex nature, non-verbal communication has not been easily or frequently operationalized (for example, Burgoon & Hale, 1987; Kahn, 1970; Riggio, 2006), and even less so in the context of the Mexican culture, which is characterized by the great importance of personal relationships (Díaz, 1994). Thus, the aim of this study is to develop and validate two self-reports on participants’ perspectives of messages received based on their partners’ non-verbal behavior. The study used a non-probability sample of 367 adults with partners in Mexico City, who responded to the “Non-Verbal Communication Scale – Perception” and the “Non-Verbal Communication Scale – Interpretation” self-reports. The results showed two valid and reliable measures whose factors were strongly supported by the literature on personal relationships and communication.